P044 Effect of specialized 6-month ADL training with subsequent a 6-month follow-up period in patients with myositis – preliminary data. (March 2019) - Spiritovic, M; Oreska, S; Storkanova, H; Hermankova, B; Cesak, P; Rathouska, A; Kubinova, K; Klein, M; Vernerova, L; Ruzickova, O; Mann, H; Pavelka, K; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Idiopathic inflammatory myopathies (IIM) are accompanied by muscular weakness caused by inflammation and immune changes in affected muscles, resulting in reduced quality of life. The aim of our study was to determine the effect of ADL training on muscle strength and endurance and quality of life of IIM patients. Objectives: The study included a total of 50 IIM patients who fulfilled the Bohan and Peter 1975 criteria and had skeletal muscle involvement. 27 patients were recruited into the intervention group (IG) and 23 patients into the control group (CG). Both groups received an educational material for home exercise, but only the IG underwent a 6 month intervention with a subsequent 6 month follow-up period. Methods: Patients were assessed by a physician and a physiotherapist blinded to intervention at months 0, 3, 6, and 12, and parameters evaluating quality of life, muscle strength and endurance were recorded. Patients also filled out PRO (patient reported outcomes) questionnaires and provided blood for routine laboratory analysis and bio-banking. Data analysis was performed between groups and within the group. Results: Compared to the observed statistically significant deterioration in the CG over the intervention period of 0–6 months, we found a statistically significant improvement in the IG in objectively assessed strength and endurance of muscles as well as in subjectively assessed functional abilities and depression. During the follow-up period, there was a significant deterioration or stagnation of the achieved positive results in the IG. However, improved functional ability during the intervention period persisted in the IG in the follow-up period as well. Only numerical improvements in the IG during the intervention compared to the numerical deterioration in CG, that did not reach statistical significance, were observed in some subjectively assessed domains of QoL (SF-36) and fatigue (FIS – in physical dimension). Conclusions: Our specialized ADL training led to a significant improvement in the observed parameters that was clinically significant in a substantial proportion of patients, and prevention of the expected worsening of muscle weakness and quality of life. Acknowledgements: Supported by AZV-16-33574A, SVV for FTVS UK 2019-260466, MHCR 023728. Disclosure of Interest: None declared.